Highly volatile constituents of Vetiveria zizanioides roots grown under different cultivation conditions - Pripdeevech P. (2014)
Roots of Vetiveria zizanioides Nash (Mae Hae; Thai ecotype) planted in three different cultivation systems (normal soil, normal soil with added microbes and semihydroponically) were extracted using a simultaneous steam distillation and solvent extraction (SDE) apparatus. Yields of the essential oils obtained were 0.27, 0.18 and 0.06%, respectively. The separation profiles obtained by comprehensive two-dimensional gas chromatography (GCxGC) and solid phase microextraction (SPME)-GCxGC analyses of the crude essential oils showed a total of 156 and 48 well-resolved components, respectively. The highly volatile fractions isolated from the three essential oils by SPME were subjected to analysis by GC-MS and 42 compounds were identified in total. Volatile component profiles of the oils obtained by normal soil and semi-hydroponic cultivation were similar, whereas a quantitative difference was noted in some major volatiles when the cultivation system containing microbes was utilized. © 2006 by MDPI.